Activity limitation and participation restriction in veterans of Indian Armed Forces: A cross-sectional study - V. K. Sashindran; Puja Dudeja; Vivek Aggarwal (Wolters Kluwer Medknow Publications, 2019)
Introduction: The armed forces provide lifelong medical benefits to all their veterans. As most of them are older, their health needs are quite different from those of serving personnel. Having led a relatively active and disciplined life in the services, their general health might also be better than that of their civilian counterparts. Unfortunately, there are no data available on the health of Indian military veterans. This study was planned to ascertain the level of activity limitation (AL) and participation restriction (PR) and determine factors affecting AL and PR. Material and Methods: This community-based, cross-sectional study was conducted among 406 veterans and their spouses aged 60 years and above residing in an urban housing society. House-to-house surveys were conducted. The study was done over 6 months (July-December 2016). Ethical clearance and informed consent were taken. The questionnaire used in the study was designed by incorporating elements from the International Classification of Functioning, Disability, and Health questionnaire and the WHO Disability Assessment Schedule. Results: Of the 406 veterans and their spouses surveyed, 188 (46.3%) were male and 218 (53.7%) were female. The majority of them were in the age groups of 61-70 years (175, 43.1%) and 71-80 years (173, 42.6%). Most of them were living with other family members with only 59 (14.5%) living alone. AL score was good or average in most of them (263 and 124, respectively), and it was bad or very bad in only a small number (11 and 8, respectively) Similarly, the PR score was good or average in 316 and 78 participants, respectively. Only 12 (2.8%) had a bad PR score. PR score increased significantly beyond the age of 80 years (P = 0.00). AL was more in males as compared to females. PR was more in those who were not married/divorced/single (P < 0.05). AL and PR were independent of the type of caregivers (P > 0.05). The most common ailments reported by males were body aches and pains, hearing defects, and problems related to micturition. Complaints of feeling low or depressed were significantly higher in females (P < 0.05). The top five causes of morbidity in the study population were hypertension (209, 51.5%), diabetes (125, 30.8%), defective vision (116, 28.6%), cataract (105, 25.9%), and dental problems (102, 25.1%). Conclusion: This study provides an insight into the magnitude of disease, impairment, and disability among veterans. Hypertension was the most common morbidity. Assessment of the AL and PR is useful planning geriatric care and educating caregivers and families to improve the quality of life of the elders.